2021
DOI: 10.1111/scd.12563
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and oral health‐related quality of life in children with attention‐deficit hyperactivity disorder and oppositional defiant disorder

Abstract: Aims Oral diseases can affect various aspects of life in patients with attention deficit hyperactivity disorder/oppositional defiant disorder (ADHD/ODD). This study aimed to assess the oral health status and oral health‐related quality of life (OHRQOL) in ADHD/ODD children. Methods Forty ADHD/ODD and 80 control children aged 3‐7 years old were included in the study. Gingival index (GI), dmft score, and the pediatric oral health‐related quality of life (POQL) questionnaire were used to determine the oral health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Thus, the whole experience of the dental GA may have been more distressing for these children. Indeed, it has recently been reported that conditions such as ADHD do impact children’s OHRQoL (Jamali et al 2021 ). A further explanation may be the increased waiting time for combination care, which could have a negative impact.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the whole experience of the dental GA may have been more distressing for these children. Indeed, it has recently been reported that conditions such as ADHD do impact children’s OHRQoL (Jamali et al 2021 ). A further explanation may be the increased waiting time for combination care, which could have a negative impact.…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation, the included participants were not screened for background anxiety disorders. [32][33][34][35] The third limitation, as in other cross-sectional studies, was the evaluation of a particular population at specific time periods. The course of the COVID-19 pandemic varies considerably among countries, regions, and even cities and thus countries have developed different strategies to prevent the spread of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (n = 4) found no significant difference in parent-reported physical HRQoL in children with ADHD compared to children without ADHD (Bussing et al, 2010;Kandemir et al, 2014;Larsen et al, 2021;Marques et al, 2013). Jamali et al (2021), who examined the oral HRQoL among children with ADHD compared to children without ADHD, found significantly more decayed, missing, or filled teeth among children with ADHD than children without ADHD, and significantly lower scores across all domains of oral HRQoL (Jamali et al, 2021). Similarly, Maden and Gamlı (2022) reported poorer oral HRQoL in children with ADHD than those without ADHD.…”
Section: Parent-reported Hrqol Of Children With Adhd Compared Tomentioning
confidence: 94%